Evaluation of combination product (Indoxacarb 5% + Fipronil 5% SC) against jassid, Amrasca biguttula biguttula and whitefly, Bemisia tabaci in cotton - BAJYA, D R; RANJITH, M; LAKHARAN, M C (The Indian Journal of Agricultural Sciences, 2015)
Field studies were undertaken at research farm, IPFT, Gurgaon to evaluate the efficacy of indoxacarb 5% + fipronil 5% SC at four doses, viz. 100 (50+50) g a.i./ha ,125 (62.5+62.5) g a.i./ha, 150 (75+75) g a.i./ha and 250 (125+125) g a.i./ha, along with fipronil 5% SC @ 100 g a.i./ha, indoxacarb 14.5% SC @ 75 g a.i./ha and Chlorpyrifos 16% + Alphacypermethrin 1% EC @ 425 (400+25) g a.i./ ha against jassids and whiteflies in cotton during kharif, 2013-14 and kharif, 2014-15. Indoxacarb 5% + fipronil 5% SC @ 125 g a.i./ha was highly effective in suppressing the population of jassids and whiteflies, resulting in 1.00, 0.67 and 1.07, 0.67 mean population of jassids and whiteflies during first and second season respectively and was on par with the higher doses of Indoxacarb 5% + fipronil 5% SC during both the seasons.